Civic media literacies: re-Imagining engagement for civic intentionality*. Issue 2 (3rd April 2018) - Mihailidis, Paul
ABSTRACT: This paper explores the structural constraints of contemporary approaches to media literacy in the face of increased partisanship, tribalism, and distrust. In the midst of a renewed call for media literacy initiatives that respond to the increasing levels of distrust in both legacy and grassroots media, this paper argues that media literacy interventions must be re-imagined as intentionally civic. A new set of emerging norms of digital culture further put into question the relevance of long-standing approaches to media literacy pedagogy and practice. This essay puts forward a new set of constructs that position media literacy initiatives to 'produce and reproduce the sense of being in the world with others toward common good' (Gordon, E., and P. Mihailidis. 2016. "Introduction." In Civic Media: Technology, Design, Practice, edited by E. Gordon and P. Mihailidis. Cambridge: MIT Press, 2). These constructs – agency, caring, critical consciousness, persistence, and emancipation – reframe media literacy as relevant to the social, political, and technological realities of contemporary life.